Hermann (Hugh) Blaschko (1900–1993): His fundamental contributions to biochemical pharmacology and clinical medicine. (August 2019) - Rubin, Ronald P
Hermann (Hugh) Blaschko was a biochemical pharmacologist best known for discovering how adrenaline (epinephrine), noradrenaline (norepinephrine), and dopamine were synthesized, stored, and metabolized in adrenomedullary cells and sympathetic nerves. Blaschko's work not only supported the validity of the concept of neurochemical synaptic transmission but he also made fundamental contributions to the development of drugs used in clinical medicine to treat diseases such as depression, hypertension, and Parkinson's Disease.